2021
DOI: 10.5219/1455
|View full text |Cite
|
Sign up to set email alerts
|

A pilot plant scale of Yellow Konjac (Amorphophallus muelleri Blume) flour production by a centrifugal mill using response surface methodology

Abstract: This study aimed at investigating the effects of polishing conditions on the physicochemical properties of polished yellow konjac flour (PYKF) with a centrifugal mill using Central Composite Design-Response Surface Methodology (CCD-RSM). Micro-mill milled yellow konjac flour (MMYKF) mass and polishing cycles were the independent variables, with four observed responses (calcium oxalate, viscosity, degree of whiteness (DoW), and glucomannan). The lower limit (-1) and upper limit (+1) for MMYKF mass in this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The results of this analysis, have differences from the research conducted by Laignier et al (2022) [9], where the crude fiber of konjac flour was 4.18%. Differences were also according to Witoyo et al [22] that found that the yellow konjac flour have 5.598% of starch and amylose 16.948% In the same study, the results of white konjac tuber were also obtained, where the starch obtained was 47.554%, amylose 17.536%, and amylopectin 30.018%. These results show differences, when compared with the results of the raw material analysis carried out in this study.…”
Section: Raw Materials Characteristicsmentioning
confidence: 60%
See 1 more Smart Citation
“…The results of this analysis, have differences from the research conducted by Laignier et al (2022) [9], where the crude fiber of konjac flour was 4.18%. Differences were also according to Witoyo et al [22] that found that the yellow konjac flour have 5.598% of starch and amylose 16.948% In the same study, the results of white konjac tuber were also obtained, where the starch obtained was 47.554%, amylose 17.536%, and amylopectin 30.018%. These results show differences, when compared with the results of the raw material analysis carried out in this study.…”
Section: Raw Materials Characteristicsmentioning
confidence: 60%
“…Variations in flour ratio and concentrate proportion have a significant effect on the texture of cookies. According to Witoyo et al (2020) [22] the main content in konjac tubers is glucomanan. Glucomanan has special properties, such as being able to form a thick solution in water, being able to expand with great swelling power, being able to form a gel, being able to form a thin, impermeable layer of water with glycerin.…”
Section: Figure 1 Sensory Properties Of Cookie Was Affected By Intera...mentioning
confidence: 99%
“…Moreover, all the responses had R 2 ≥ 0.6536, adjusted R 2 ≥ 0.2083, adequate precision ≥ 4.1399, and lack of fit ≥ 0.0287. The high R 2 and adjusted R 2 demonstrated that the quadratic model adequately explained the variance of all response data [31,32]. Furthermore, adequate precision measures the signal-to-noise ratio, where a ratio ≥ 4 indicates an adequate signal [33,34].…”
Section: Model Fittingmentioning
confidence: 90%
“…Porang flour (PF) is a processed product from native porang (Amorphophallus muelleri Blume) tubers from Indonesia with a characteristic yellow color on their tubers [3][4][5]. This flour has unique characteristics and has been applied in various food industries for thickeners, binders, fat substitutes, and other purposes.…”
Section: Introductionmentioning
confidence: 99%